NACs, generalist in plant life - Han, Kunjin; Zhao, Ye; Sun, Yuhan; Li, Yun (Plant biotechnology journal, 2023)
Summary Plant‐specific NAC proteins constitute a major transcription factor family that is well‐known for its roles in plant growth, development, and responses to abiotic and biotic stresses. In recent years, there has been significant progress in understanding the functions of NAC proteins. NAC proteins have a highly conserved DNA‐binding domain; however, their functions are diverse. Previous understanding of the structure of NAC transcription factors can be used as the basis for their functional diversity. NAC transcription factors consist of a target‐binding domain at the N‐terminus and a highly versatile C‐terminal domain that interacts with other proteins. A growing body of research on NAC transcription factors helps us comprehend the intricate signalling network and transcriptional reprogramming facilitated by NAC‐mediated complexes. However, most studies of NAC proteins have been limited to a single function. Here, we discuss the upstream regulators, regulatory components and targets of NAC in the context of their prospective roles in plant improvement strategies via biotechnology intervention, highlighting the importance of the NAC transcription factor family in plants and the need for further research.